2020
DOI: 10.1021/acs.jmedchem.0c01457
|View full text |Cite
|
Sign up to set email alerts
|

N-Trifluoromethyl Amines and Azoles: An Underexplored Functional Group in the Medicinal Chemist’s Toolbox

Abstract: Introducing trifluoromethyl groups is a common strategy to improve the properties of biologically active compounds. However, N-trifluoromethyl moieties on amines and azoles are very rarely used. To evaluate their suitability in drug design, we synthesized a series of N-trifluoromethyl amines and azoles, determined their stability in aqueous media, and investigated their properties. We show that N-trifluoromethyl amines are prone to hydrolysis, whereas N-trifluoromethyl azoles have excellent aqueous stability. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 73 publications
0
53
0
1
Order By: Relevance
“…As it was mentioned in the Introduction, these include, for example, sulfoximines, [39,527,528] sulfonimidamides [529,530] and their analogs, [531] dialkyl phospine oxides [40,145] -unusual isosteres of amides, sulfonamides, sulfones, and related compounds (Figure 13), as well as deuterated analogues, [41] silicon-containing isosteres, [42] or Ntrifluoromethylated azoles. [43] It is interesting to note that nearly all these examples, as well as most of those discussed in this review, originate from organosulfur, -boron, -phosphorus, -silicon, or -fluorine chemistry. We believe that early drug discovery will continue to benefit from these and related areas of organo-element chemistry, and more neglected chemotypes will be uncovered in the nearest future.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…As it was mentioned in the Introduction, these include, for example, sulfoximines, [39,527,528] sulfonimidamides [529,530] and their analogs, [531] dialkyl phospine oxides [40,145] -unusual isosteres of amides, sulfonamides, sulfones, and related compounds (Figure 13), as well as deuterated analogues, [41] silicon-containing isosteres, [42] or Ntrifluoromethylated azoles. [43] It is interesting to note that nearly all these examples, as well as most of those discussed in this review, originate from organosulfur, -boron, -phosphorus, -silicon, or -fluorine chemistry. We believe that early drug discovery will continue to benefit from these and related areas of organo-element chemistry, and more neglected chemotypes will be uncovered in the nearest future.…”
Section: Discussionmentioning
confidence: 92%
“…Such emerging motifs are represented by boronic acids as the covalent warheads, [36] unusual fluorinecontaining aliphatic substituents, [37,38] sulfoximines, [39] phosphine oxides, [40] deuterated substituents, [41] silicon-containing isosteres, [42] or N-trifluoromethylated azoles. [43] Evolution of all three types of emerging building blocks for medicinal chemistry can be schematically represented by "the building block triangle" (visually similar to high-throughput screening (HTS) triangle [44] or principal moment of inertia (PMI) plots [45] ) (Figure 2). The vertices of this triangle correspond to the building blocks with functional groups for novel synthetic methodologies, novel sp 3 -enriched carbo-and heteroaliphatic cores, and emerging medicinal chemistry motifs, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…For the first time, this functional group has become readily accessible using mild conditions, without the need for hazardous reagents or elaborate prefunctionalization. We set out to investigate the aqueous stability and in vitro properties of this compound class to judge its suitability for application in medicinal chemistry [6]. We found that tertiary N-trifluoromethyl N-alkyl amines, including benzyl amines and anilines, rapidly hydrolyze in aqueous media.…”
Section: Trifluoromethylated Amines Azoles Amides and Aryl Selenium Dmentioning
confidence: 99%
“…Azoles earn an important place in the fields of biology, pharmaceuticals, functional materials, and organic synthesis [1] . Because the incorporation of a trifluoromethyl (CF 3 ) group onto the nitrogen can largely decrease the basicity, thereby improving the metabolic stability, lipophilicity or bioavailability of lead compounds, [2] N ‐CF 3 azole cores have become highly pursued targets, especially in the medicinal chemist's toolbox [3, 4] . By contrast to the most prevalence of N ‐methyl azoles, N ‐trifluoromethyl azoles are not yet routinely used in drug discovery though studies have shown that the replacement of the N ‐methyl by the N ‐trifluoromethyl could lead to significantly increased bioactivities of azole derivatives (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…This type of fluorination‐based strategy has been used for accessing N ‐CF 3 azoles (Scheme 1 A). [3, 5, 6b–d] However, limited examples are available because the methodology shares the fundamental limitations of unavoidably requiring both tedious N ‐pre‐functionalization and unfriendly reagents. By comparison, direct introduction of the CF 3 onto the heterocyclic nitrogen allows for economic and convenient entry to N ‐CF 3 azoles.…”
Section: Introductionmentioning
confidence: 99%